Faktor-faktor yang mempengaruhi Performance Antenna: Beamwidth, Gain dan Pola radiasi - Brahmana, Steven Brema; Kuntadi, Cris; Sukarwoto; Anwar, Syairi; Supriyadi (Journal of Engineering and Transportation, 2023)
Antennas are critical components in communication and radar systems. Factors that affectAntenna Performance, namely Beamwidth, Gain and Radiation pattern, a human resourcemanagement literature study. The purpose of writing this article is to build hypotheses ofinfluence between variables to be used in further research. The results of this literature reviewarticle are: 1) Beamwidth affects Antenna Performance; 2) Gain affects AntennaPerformance; and 3) Radiation pattern affects Antenna Performance.Purpose – The purpose of writing this article is to build hypotheses of influence betweenAntenna Performance namely Beamwidth, Gain and Radiation patternDesign/methodology/approach – – The method of writing this scientific article is aqualitative method and library research that examines the theory and relationship or influencebetween variables from books and journals both offline in the library and online.Findings – The results of this literature review article are: 1) Beamwidth affects AntennaPerformance; 2) Gain affects Antenna Performance; and 3) Radiation pattern affectsAntenna Performance.Research limitations/implications – There are other factors that can affect AntennaPerformance other than Beamwidth, Gain and Radiation patternPractical implications – It helps to provide a deeper understanding of the factors AntennaPerformance and find other factors that can affect Antenna PerformanceOriginality/value – Strengthen the theory and phenomenon of the relationship or influencebetween Antenna Performance, Beamwidth, Gain and Radiation pattern